A π-extended phenanthrene-fused aza[7]helicenium as a novel chiroptically-active architecture in organic and aqueous media. Issue 3 (21st December 2022) - Olivier, Céline; Nagatomo, Nao; Mori, Tadashi; McClenaghan, Nathan; Jonusauskas, Gediminas; Kauffmann, Brice; Kuwahara, Yutaka; Takafuji, Makoto; Ihara, Hirotaka; Ferrand, Yann
Abstract : The synthesis and characterization of an original π-extended cationic azahelicene is reported. Abstract : The synthesis and characterization of an original π-extended cationic azahelicene is reported. The phenanthrene-fused aza[7]helicene derivative encompasses a total of ten aromatic fused rings leading to a dissymmetric yet helically folded structure, as revealed by NMR and X-ray diffraction analyses. The polyaromatic and cationic nature of the new azahelicenium makes it soluble in both organic and aqueous media, which allowed photophysical studies in solvents of different polarities. The extended chromophoric species demonstrates a broad absorption over the whole visible range and orange-red fluorescence emission. Chiral resolution of the racemate was performed subsequently, affording two optically pure and configurationally stable azahelicenium enantiomers. Multi-band circular dichroism and long-wavelength circularly polarized emission were observed, associated with remarkable absorption and luminescence dissymmetry factors, both in organic and aqueous media.